New essays on Tarski and philosophy - Patterson, Douglas (Oxford : Oxford University Press, 2008)
'Tarski and Philosophy' shows the way to a proper understanding of the philosophical legacy of the great logician, philosopher and mathematician Alfred Tarski (1902-1983).
Description based on print version record.
Includes bibliographical references and index.
Keywords: Tarski, Alfred; Mathematics -- Philosophy; Logic, Symbolic and mathematical -- Philosophy